Simultaneous determination of nine endogenous steroids in human urine by polymeric-mixed micelle capillary electrophoresis - Flor, Sabrina Andrea (2010)
A new CE system based on the use of polymeric-mixed micelles (cholic acid, SDS and the poloxamine Tetronic® 1107) was developed for the simultaneous determination of nine steroids in human urine. This method allows the baseline separation and quantitation of cortisol, androstenedione, estriol, dehydroepiandrosterone sulfate, testosterone, dehydroepiandrosterone, estrone, progesterone and estradiol in less than 25 min showing to be sensitive enough to detect low concentrations of these steroids in urine samples (5–45 ng/mL). The optimized electrophoretic conditions were performed using a 50 cm×75 μm capillary, 18 kV, 25°C, with 44 mM cholic acid, 10 mM SDS, 0.05% w/v tetronic® 1107, 2.5% v/v methanol, 2.5% v/v tetrahydrofuran in 5 mM borate – 5 mM phosphate buffer (pH=8.0) as a background electrolyte and a dual 210/254 UV-detection. The method can simultaneously determine 0.1–120 μg/mL, which corresponds to 5–6000 ng/mL of steroids in 2 mL urine. The recoveries ranged between 82.4 and 101.5%. Due to its simplicity, speed, accuracy and reliability, the proposed method could be a potential alternative to the traditional methodologies used with clinical purposes.